Comparison of cold knife tonsillectomy versus thermal welding tonsillectomy in adults: a prospective trial - Hancı, Deniz; Altun, Hüseyin (ENT Updates, 2015)
Objective: The aim of this prospective study was to compare the duration and the postoperative complaints of the patients who had tonsillectomies with cold knife vs thermal welding. Methods: Thirty-one adults undergoing tonsillectomy were included. Traditional tonsillectomy was implemented in one tonsil, and thermal welding tonsillectomy (TWT) was implemented in other tonsil of the same patient. Duration of the operation, amounts of blood loss and morbidity (postoperative pain) were recorded. Results: Degree of pain, as assessed by Visual Analogue Scale, within the 1st postoperative day was not different between the two groups. Sensation of pain in 2nd–14th days were significantly lower in TWT group than in traditional tonsillectomy group. Although sensation of throat swelling and difficulty in eating tended to be lower in TWT group than in traditional tonsillectomy group, difference was not statistically significant. Although degree of ear ache on TWT side tended to be lower than traditional tonsillectomy side, difference was not statistically significant. In terms of postoperative hemorrhage, there was no difference between two tonsillectomy techniques. Duration of operation was significantly lower in TWT group than in traditional tonsillectomy group. Conclusion: TWT results in decreased postoperative pain and significantly shortened operation time compared to the traditional tonsillectomy. Therefore, we suggest that TWT is a quite effective in tonsillectomy procedure.